Improving Students’ Writing Ability in Procedure Text Through Make-A-Match Technique at Ninth Grade of SMPN Satu Atap 1 Jabiren Raya - Marcelina, Marcelina; Sabarun, Sabarun; Mirza, Akhmad Ali (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The study's aims are to examine the improvement of process text writing ability with Make-a-Match technique and to discover the benefits and drawbacks of using Make-a-Match technique in increasing procedure text writing ability at SMPN Satu Atap 1 Jabiren Raya's Ninth Grade. Twenty students participated in the study. The study's instruments included interview questions, an observation list, a pre-test, and two post-tests. This was an action research study. The study was completed in two rounds. There were four steps in each cycle: planning, implementation, observation, and reflection. The findings demonstrated that students' learning outcomes increased after using the Make-a-Match type cooperative learning approach. The average score in the first cycle test was 54.55, with a post-test score of 70.95, and an average score of 84.45 in the second cycle. In cycle I, 35% of students met the target, while in cycle II, 90% of post-test I and II findings showed an improvement in student learning outcomes.